Measurement of the binding properties of meat used in restructured beef products - Goll, S.J.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The dried weight of the material washed from meat surfaces by distilled water closely paralleled the binding strength between meat particles as measured by tensile strength testing. Sponges added to meat pieces during mixing were a poor estimation of protein extraction and binding strength.
Keywords: Beef; Meat binding; Restructured beef products